Enhancement of microstructure and initial permeability due to Cu substitution in Ni0.50-xCuxZn0.50Fe 2O4 ferrites - Rahman, M.L.; Akther Hossain, A. K M (© 2011 Elsevier, 2016)
This article was published in the Journal of Magnetism and Magnetic Materials [© 2011 Elsevier B.V.] and the definite version is available at : http://dx.doi.org/10.1016/j.jmmm.2011.02.031 The Journal's website is at: http://www.sciencedirect.com/science/article/pii/S0304885311001417